2012
DOI: 10.1108/13565361211219202
|View full text |Cite
|
Sign up to set email alerts
|

A review on effect of minor alloying elements on thermal cycling and drop impact reliability of low‐Ag Sn‐Ag‐Cu solder joints

Abstract: Purpose -The purpose of this paper is to discuss the reliability of board level Sn-Ag-Cu (SAC) solder joints in terms of both thermal cycling and drop impact loading conditions, and further modification of the characteristics of low Ag-content SAC solder joints using minor alloying elements to withstand both thermal cycle and drop impact loads. Design/methodology/approach -The thermal cycling and drop impact reliability of different Ag-content SAC bulk solder will be discussed from the viewpoints of mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Wang et al [ 17 , 18 ] studied the Sn–Ag–Cu Ternary Metal Coating Solder, they found that with the increase of Ag content, the elongation will decrease obviously, and the alloy strength will increase. This is because the number of Ag 3 Sn particles will increase during the aging process, causing cracks to form along the particle interface [ 19 ] found poor thermal cycling performance and impact resistance of low silver content Sn–Ag–Cu solders. After adding Cu components to Sn–Ag–Cu solder, the comprehensive properties of all aspects have been greatly improved, but the wettability has decreased significantly high, which is quite different from Sn–Pb solder [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 17 , 18 ] studied the Sn–Ag–Cu Ternary Metal Coating Solder, they found that with the increase of Ag content, the elongation will decrease obviously, and the alloy strength will increase. This is because the number of Ag 3 Sn particles will increase during the aging process, causing cracks to form along the particle interface [ 19 ] found poor thermal cycling performance and impact resistance of low silver content Sn–Ag–Cu solders. After adding Cu components to Sn–Ag–Cu solder, the comprehensive properties of all aspects have been greatly improved, but the wettability has decreased significantly high, which is quite different from Sn–Pb solder [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…These stresses are induced in solder joints due to the different coefficients of thermal expansion of electronic components and circuit board on which solder joint is made [5]. Solder joints are also responsible for keeping the electronic components intact, which means they must possess excellent mechanical and thermo-mechanical properties to support the components [6].…”
Section: Introductionmentioning
confidence: 99%